2009
DOI: 10.1111/j.1742-7843.2008.00358.x
|View full text |Cite
|
Sign up to set email alerts
|

Procyanidins Produce Significant Attenuation of Doxorubicin‐Induced Cardiotoxicity via Suppression of Oxidative Stress

Abstract: Doxorubicin is widely prescribed in the chemotherapy of haematological malignancies and solid tumours. The major side effect of doxorubicin is oxidative injury-related cardiotoxicity, which has dramatically hindered its usage. Procyanidins from grape seeds are potent free radical scavengers that have been shown to protect against anthracyclineinduced cardiotoxicity. In the present study, we tested whether procyanidins would prevent the doxorubicin-induced cardiotoxicity in rats. Rats were intraperitoneally tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 31 publications
4
24
0
1
Order By: Relevance
“…17,18,[25][26][27] Alterations in physiological parameters are well known as one of the toxic effects of DOX, which is characterized by reduced body and heart weights. [28][29][30] Our findings here confirmed the literature reports that DOX treatment leads to decreased both body and heart weights in animals 31 and that GSE treatment increased body and heart weights, as compared to DOX group. Our data supported previous findings in which DOX administration significantly resulted in increased left ventricular dysfunction and decreased the FS and EF in the echocardiographic assessment.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…17,18,[25][26][27] Alterations in physiological parameters are well known as one of the toxic effects of DOX, which is characterized by reduced body and heart weights. [28][29][30] Our findings here confirmed the literature reports that DOX treatment leads to decreased both body and heart weights in animals 31 and that GSE treatment increased body and heart weights, as compared to DOX group. Our data supported previous findings in which DOX administration significantly resulted in increased left ventricular dysfunction and decreased the FS and EF in the echocardiographic assessment.…”
Section: Discussionsupporting
confidence: 82%
“…50 In addition, it was reported that procyanidin, an antioxidant flavonoid of the GSE, exhibited antitumor activity on MCF7 cells. In this regard, other studies have demonstrated that procyanidins induce cytotoxicity on several tumor cells such as human adenocarcinoma cells A549, 31 human colorectal cancer HT29, LoVo cells, 51 A-427 human lung cancer cells, CRL-1739 human gastric adenocarcinoma cells and K562 chronic myelogenous leukemic cells. 52 During the two past decades tremendous effort has been put into uncovering the molecular mechanisms and/or intracellular targets involved in the DOX-induced cardiotoxicity and different hypotheses have been developed to explain this phenomenon, [53][54][55] but no single one of these was able to fully explain it.…”
Section: Cardioprotective Effect Of Grape Seed Extractmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that GSPE conferred cardio protection against exogenous H 2 O 2 _ and antimycin A-induced oxidant injury by reactive oxygen species scavenging and iron chelating (Shao et al 2003). More reports stated that procyanidins could play a part in the cardiac protective effect by suppressing of oxidative stress (Li et al 2009). …”
Section: Groups Ldh(u/l) Alt(u/l) Ast (U/l) Ck (U/l)mentioning
confidence: 99%
“…ROS generated during cancer chemotherapy may also decrease the efficacy of the treatment by interfering with drug induced apoptosis and cell cycle progression, which are optimal effect on cancer cells [6] [7]. Doxorubicin (DOX) is one of the most widely used and successful chemotherapeutic anti-tumour drugs prescribed in hematological malignancies and solid tumors [8]. Its clinical application is limited due to its cumulative dose-related cell toxicity.…”
Section: Introductionmentioning
confidence: 99%